Very long-chain fatty acids accumulate in breast cancer tissue and serum - Alicja Pakiet; Michalina Ciosek; Oliwia Lange; Katarzyna Duzowska; Agata Janczy; Małgorzata Kapusta; Yelyzaveta Razghonova; Marcin Ekman; Anna Abacajew-Chmyłko; Paweł Kabata; Adriana Mika (Cancer Cell International)
Abstract Background Breast cancer (BC) remains one of the most common cancers with relatively high mortality and is associated with alterations in fatty acid (FA) metabolism. While typical FAs have been extensively studied, there is increasing evidence for a potential role of very long chain fatty acids (VLCFAs) in cancer growth and progression. Methods This study involved 54 BC patients from whom samples of malignant tumor, normal fibroglandular tissue, and breast adipose tissue were collected. Their FA content was analyzed by gas chromatography-mass spectrometry. The expression of fatty acid elongases (ELOVLs) and FA-transporting proteins was analyzed in the tissues by RT-PCR and immunofluorescence. Results: Higher levels of saturated and monounsaturated VLCFAs were found in BC tissues compared to normal tissues (p < 0.001) and in patients’ blood compared to healthy controls blood (p < 0.001). However, the level of VLCFAs was lower in BC adipose tissue compared to healthy control adipose tissue (p < 0.001). Interestingly, there were no obvious differences in ELOVL1 mRNA or protein levels between normal and cancer tissues. Conclusions: Elevated levels of VLCFAs in BC tissue are the result of lipid uptake from outside the tumor rather than in situ synthesis.